Commitments and accountability: Peru’s unique nutrition journey - Yosef, Sivan; Goulden, Jay (International Food Policy Research Institute, 2016)
PERUVIANS HAVE MUCH to celebrate in regards to the rapid progress the country has made in reducing malnutrition. In 2013, only 3.5 percent of children under five years of age in Peru were underweight. Even smaller proportions— 0.5 percent and 0.1 percent—were moderately or severely wasted. But the statistic that many nutritionists point to when lauding the country as a nutrition success is Peru’s rate of childhood stunting (Figure 14.1). In 2014, 14.6 percent of children under five years of age were stunted. While this rate is not as low as the country’s other nutrition indicators, it reflects a remarkable improvement. Less than a decade earlier, the prevalence was twice as high (29.5 percent).4 How was this rapid progress achieved—not only at a national level, but across all of Peru’s diverse regions, even poor rural ones including the Andean Highlands, and even amongst the poorest 20 percent of the population?